2016
DOI: 10.1039/c5cp05132k
|View full text |Cite
|
Sign up to set email alerts
|

Pair correlations that link the hydrophobic and Hofmeister effects

Abstract: The Hofmeister effect describes how different ions make solutes more or less hydrophobic. The effect is thought to occur due to structural changes in the solvent induced by the ion's presence, particularly in water. In this study, the structural changes in water due to the presence of ions are investigated by molecular dynamics simulations of various monatomic ions in the SPC/E water model. Structural analyses reveal specific orientations of solvating waters around each of the ions studied. Using a new method,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 72 publications
1
7
0
Order By: Relevance
“…Recently, the influence of various atomic ions on water's long-range dipolar correlations was reported, 62 where it was found that the presence of a single ion can modulate the pair correlations that contribute to the hydrophobic effect. 36 Furthermore, the ion's presence induces new correlations between permanent dipole moments and the ion itself; the free energy of which results in a Hofmeister series for different ions, 62 demonstrating specific ion effects with respect to dipole-ion correlations. Here, the interest is on the structure and lengthscale of the perturbation of water's structure induced by an ion's presence, as found in similar dipole correlations to those in φ MD (r).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, the influence of various atomic ions on water's long-range dipolar correlations was reported, 62 where it was found that the presence of a single ion can modulate the pair correlations that contribute to the hydrophobic effect. 36 Furthermore, the ion's presence induces new correlations between permanent dipole moments and the ion itself; the free energy of which results in a Hofmeister series for different ions, 62 demonstrating specific ion effects with respect to dipole-ion correlations. Here, the interest is on the structure and lengthscale of the perturbation of water's structure induced by an ion's presence, as found in similar dipole correlations to those in φ MD (r).…”
Section: Resultsmentioning
confidence: 99%
“…Following the treatment by Besford et al, 62 the contribution of ψ MD (r) to the solvation free energy of the chloride ion may be given as…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We label φ M D (r) with a subscript "MD", to signify that it is calculated from simulated trajectories. The φ M D (r) interaction is always negative, so it produces an attractive force between pairs of polar molecules, which has been shown to contribute to the entropy of hydrophobic solvation, 59 to contribute to the long-range structure of polar liquids, including liquid water, 63 to be selectively modulated by different ions, 64 and to produce a stabilizing force at the water-vapor interface. 60 It is therefore of interest to compare the strength of this interaction when water molecules are constrained in their orientation by the quartz interface.…”
Section: Resultsmentioning
confidence: 99%